The model decision support system on revealing of subjects of threats in territory of the airport - Лобанчикова, Н. М. (Problems of Informatization and Control, 2009)
Presents conceptual decision support system construction positions on revealing the subjects of emergency situations threats in the territory of the airport in the form of structural models and algorithms of functioning decision support system